The Impact of Technically-Oriented Lean Production Practices on Operational Performances in Malaysian Manufacturing Industries - Iteng, Rosman; Ahmad, Mohd Akhir (UUM Press, 2017)
The primary purpose of this paper is to investigate the relationships between technically-oriented lean production practices and operational performance in Malaysian manufacturing industries. Grounded by the Socio-technical System Theory and the Program Theory, this study formulates and examines a conceptual model that links technically-oriented lean production practices and operational performance. This study utilizes two hundred and five manufacturing companies, selected randomly from the Federation of Malaysian Manufacturers Directory. The study measures senior production or lean managers perception of the lean production practices and the level of operational performances in their companies. This study applies SPSS package for data analysis. The result indicates that technically-oriented lean production practices namely quality at source, just-in time, flow system and technology & innovation are significantly associated with the operational performance of the companies. This study presents empirical evidence in the field of management, particularly in the context of operations management. The findings would further enrich the existing knowledge in this field. Finally, this study would provide useful guidance for the managers to plan and maintain lean production in the organization as well as to generate new measures of lean production in order to enhance operational performance at the company level.